The Effects of Neuro-Linguistic Programming on Inhibitory Controls to Lose Weight in Overweight Policemen - Choti, Pawarin; Haenjohn, Juthamas; Subwirapakorn , Warakorn (Journal of The Royal Thai Army Nurses, 2021)
The objective of this research was to develop and test the effectiveness of the inhibitory control for weight loss based on Neuro-linguistic programming training program (NLP-ICWL) in overweight policemen. The samples were policemen who had BMI more than 25 and they were divided by randomly matched pair of scores to be an experimental group and a control group, 10 policemen in each group. The research instruments were designed by the researcher: 1) the NLP-ICWL program with global unconscious reframing technique and 2) Go / No Go Task with Thai food and beverage images. The experimental group received the NLP-ICWL program for 2 sessions. The control group received only the knowledge from the balance calories, brain, mind and exercise personal book and self-training for 2 months. The assessments were done in pretest, posttest and 2 months follow-up phase. The data were analyzed by utilizing a repeated measures analysis of variance and paired-different test by Bonferroni method. The findings were revealed that the experimental group that received the NLP-ICWL program had the mean score of inhibitory control for weight loss in the follow-up and posttest higher than pretest with statistical significance at .05 level. Additionally, the experimental group had the mean score of inhibitory control for weight loss higher than those in the control group and in the follow-up and posttest with statistical significance at .05 level. Moreover, the experimental group had the mean score of body composition in the posttest and follow-up period lower than the pretest and the control group.